Nociception Before and After Exercise In Rats Bred for High and Low Aerobic Capacity - Geisser, Michael E. (2008)
Exercise and stress are known to influence pain perception. However, little is known about how level of fitness influences pain perception and the experience of pain. In the present study, pain perception before and after exercise to exhaustion was examined in 6 rats systematically bred to have a high aerobic capacity (HCR animals) and 6 rats systematically bred to have a low aerobic capacity (LCR animals). HCR animals had significantly higher pain thresholds compared to LCR animals before and after exercise (7.66 s compared to 6.01 s, t = −3.07, p < .05; and 6.89 s versus 4.73 s, t = − 3.73, p < .01, respectively). In addition, both groups of animals displayed evidence of hyperalgesia following exercise compared to baseline. However, the pain thresholds of HCR animals returned to baseline levels faster than LCR animals following exercise. The findings support the hypothesis that level of fitness plays a role in the perception of pain. In addition, a higher level of fitness may serve as buffer against the effects of stress and help to reduce or prevent the experience of clinical pain. Further research is needed to examine the mechanisms that underlie this phenomenon.